Chelonitoxism outbreak caused from consuming turtle, Eastern Samar, Philippines, August 2013 - Ray Justin Ventura; Paola Katrina Ching; Vikki Carr de los Reyes; Ma Nemia Sucaldito; Enrique Tayag (World Health Organization Regional Office for the Western Pacific, 2015)
Background: On 21 August 2013, the Event-based Surveillance and Response system of the Department of Health, Philippines captured a foodborne illness event among residents of a coastal village in Eastern Samar, Philippines. The suspected cause was the consumption of a sea turtle found near the village. A team from the Department of Health was sent to conduct an outbreak investigation. Methods: A case was defined as any person in Arteche, Eastern Samar, who developed dry mouth and burning sensation in the throat from 15 August to 27 August, 2013. Severity of the disease was classified as mild, moderate or severe. We conducted records review, environmental investigation, interviews of key informants and a retrospective cohort study. Results: Sixty-eight cases were identified; four died (case fatality rate = 6%). All cases had a history of turtle meat consumption. Dose-dependent relationship was noted between amount of turtle meat consumed and the risk of illness. In the cohort study, consumption of turtle meat and turtle meat soup were associated with illness. Conclusion: This study identified turtle meat as the source of this foodborne outbreak and emphasized the dangers of consuming turtle meat. Other reported cases of turtle meat poisoning in the Philippines suggest that turtle consumption is an ongoing practice in the country. By publishing information about sea turtle poisoning outbreaks in the Philippines, we hope to raise awareness of the potential severe health effects from ingesting these endangered sea creatures.